Mapping of reindeer ranges in the Kautokeino area, Northern Norway, by use of Landsat 5/TM data - Tømmervik, H.; Lauknes, I. (Rangifer, 1987)
The aim of this study was to test the utility of Landsat 5/TM data to detect and map reindeer ranges (winter ranges). The area which has been investigated is the Ávzze area in Kautokeino, Northern Norway, on the means of Landsat 5 TM-data. A «hybrid» non-supervised/supervised classification routine was elaborated and applied in this project. The initial stage was an analysis of several bandcombinations, and the 5/4/3 combination gave the preferable combination as input to the cluster algorithm (unsupervised classification). The image was divided in 4 sections of size 512 samples and 512 lines. One of this sections (the section which cover the ground truth map) was selected for the non-supervised classification. In the beginning 17 classes were merged, and a median filter was applied for the resultant image, which comprises 12 classes. The statistics from the final result from the non-supervised classification were then used together with the TM bandcombination 5/4/3 for the whole image, as input to the minimum distance classification algorithm. This algorithm was applied to every section in turn. A mosaic of the 4 sections was then made and a median filter was then registred to a digitalized map (UTM-pro-jection). The final result was a colored thematic map over the whole area. The classification of the scene was successful with an overall classification of 90-1 (X)% for lichen-heaths (9dx/9c/9a/9av Dry shrub, fresh shrub) and birch-forests (6d/6dv/6dx shrubtype with lichen). The condition of the lichen-heaths could be detected on a sufficient level on the basis of the satellite data, but further analysis will be done here. The accuracy of the digital classification was assessed on a quantitative basis. Visual classification and interpretation of the satellite imagery showed that areas of conflict (roads, agriculture) could be detected. In chapter 6. «Resultater og diskusjon» some other results from other studies/investigations carried out in Scandinavia concerning remote sensing in mapping of vegetation are refered and discussed. Based on this study, we will conclude that use of satellite data is capable to serve as first stage classification in a multistage land use and reindeer range inventory and monitoring system. Kartlegging av reinbeiter ved hjelp av Landsat 5/TM data i Kautokeino, Nord-Norge. Abstract in Norwegian / Sammendrag: Målet med foreliggende undersøkelse var å undersøke muligheten av bruk av satellittdata i kartlegging av vinterbeiter for rein i Ávzze-området i Kautokeino på bakgrunn av Landsat 5 TM -data. En «hybrid» klassifikasjonsrutine ble fulgt i prosjektet. Først ble en ikke styrt klassifikasjonsrutine («duster algoritme») på en 1/4 del av bildet/scenen hvor man hadde markdata (flybildetolkning av vegetasjon) utført. Ved analyse av ulike kanalkombinasjoner kom man fram til at kanalkombinasjonen TM 5/4/3 hadde størst overenstemmelse med markdata. Det klassifiserte resultatet (12 klasser) ble brukt som «inndata» i en styrt klassifikasjonsrutine («minimum dinstance» algoritme) for hele bildet/scenen. Resultatet av denne klassifikasjonen ble filtrert for enkeltpiksler («median-filter») og til slutt ble det klassifiserte bildet geometrisk transformert til UTM - kartprojeksjon. Resultatet ble dermed et tematisk kart. Klassifikasjon (ikke styrt/styrt) på scenen viste god overensstemmelse med det tolkede flybildet fra området, og klassifikasjon med hensyn til lavheier og fattige bjørkeskoger med lav, viste fra 90-100% samsvar i forhold til det tolkede flybildet. Tilstanden av lavbeitene kunne detekteres ut fra satellittdataene, men her trenges det mer bildeanalyse og feltundersøkelser. Visuell analyse viste at inngrep i beiteområdene som veier og landbruk og andre inngrep kunne tolkes ut. I kapittel 5. Resultater og diskusjon blir andre studier med henhold til satel-littkartlegging referert og diskutert. De foreliggende resultater viser at man kan bruke satellittdata som første trinns kartlegging av reinbeiter, samt til overvåking av reinbeitene over tid.